Assessing effective hydrological connectivity for floodplains with a framework integrating habitat suitability and sediment suspension behavior. (1st August 2021) - Tan, Zhiqiang; Li, Yunliang; Zhang, Qi; Liu, Xinggen; Song, Yanyan; Xue, Chenyang; Lu, Jianzhong
Highlights: Hydrodynamic parameters affects hydrological connectivity following threshold effect. Continuum is a valuable metric for recognizing potential habitat patches and links. Overlapping area between different ecological indicators' habitats varies seasonally. Abstract: Continual and accelerating declines in hydrological connectivity threaten ecosystem processes, biodiversity, and services throughout the world. Therefore, there is an increasing demand for user-driven tools that assess hydrological connectivity from an effective perspective. We developed the Connectivity ASsessment Tool 1.0 (CAST1.0), which takes the threshold behaviors of focal ecological indicators into account, allows quantifying effective hydrological connectivity and its regime shift. We illustrate the use of CAST1.0 for the case of Poyang Lake, China. It was found that the response of effective hydrological connectivity to inundation depth, flow velocity, and water temperature follows a dynamic threshold effect. The evaluation of connected objects based on specific niches provides a valuable metric for recognizing potential habitat patches and links. This study provides a sound basis for assessing hydrological connectivity in a meaningful way, promising to provide novel insights into maintaining and restoring biodiversity and associated ecosystem services around the world. Graphical abstract: Image, graphical abstract